The Influence of Perceived of Usefulness, Trust and Risk on Interest in Using Electronic Money Services in Communities in Malang City - Gabriella Sherly Violita; Anna Triwijayanti; Catharina Aprilia Hellyani (PT FORMOSA CENDEKIA GLOBAL, 2023)
The transaction process using e-money in the community in Malang City is very influential. To determine the effect of perceived usefulness, perceived trust, and perceived risk on satisfaction in the use of electronic money is the purpose of this study. The population of this study were 846,126 people in Malang City. Purposive sampling is the method used to determine the number of samples. From 846,126 people in Malang City samples, 400 people were obtained. The autocorrelation test, heteroscedasticity test, multicollinearity, and normality test are classical assumption tests conducted in this study. After testing, the conclusions that can be drawn are perceived usefulness, perceived trust, and perceived risk partially have a positive and significant influence on satisfaction in using e-money. Meanwhile, simultaneously are able to influence interest in using electronic money services by 63%.